Biometric and reproductive aspects of the pen shell Atrina seminuda (Bivalvia: Pinnidae) in northeastern Venezuela. (3rd April 2017) - Rangel, Maria Salomé; Mendoza, Jeremy; Freites, Luis; Tagliafico, Alejandro; Silva, José; Garcia, Natividad
ABSTRACT: The pen shell Atrina seminuda is a target for a small artisanal Caribbean fishery; however, little is known about its biology. The length frequency distribution, biometric relations and reproduction of this species were studied in northeastern Venezuela. Using transects selected from among 360 stations a population was sampled monthly by SCUBA diving. An analysis of 1748 individuals showed a shell height ( SH ) between 4 cm and 23.6 cm, with an average of 16.7 ± 2.5 cm. For both sexes, statistical differences in mean SH were observed (analysis of variance F  (1, 1113) = 69.538; P  < 0.001); organisms larger than 22 cm were females, whereas those between 8 and 10 cm were males. Log-linear regressions were estimated for shell length ( SL ), total weight ( TW ) and adductor muscle weight ( MW ) as a function of SH . In all cases there were statistical differences between males and females, with males presenting positive allometry and females showing isometry. Mean SH at maturity for males (8.24 cm) was lower than for females (11.88 cm), and for sexes combined was estimated at 8.71 cm. Gametogenic activity was observed throughout the year, with two main peaks of spawning (April and August/September 2008). All this information is crucial for demographic modelling and stock assessment for managing this species.